Riding the bumps in mathematics learning: Relations between academic buoyancy, engagement, and achievement. (February 2023) - Putwain, David W.; Wood, Peter
Abstract: Academic buoyancy is conceptualised as the capacity to successfully navigate the typical adversities experienced during the course of schooling. Studies have shown positive relations between academic buoyancy and beneficial achievement-related beliefs, emotions, and behaviours. Relations with achievement are often small and studies of reciprocal relations are lacking. In a sample of 1, 242 primary school students, we examined reciprocal relations between academic buoyancy, engagement, and achievement. Baseline levels of academic buoyancy and engagement positively predicted subsequent achievement. Achievement predicted gain in academic buoyancy but not engagement. Engagement, but not academic buoyancy, predicted gain in achievement. However, academic buoyancy predicted achievement gain indirectly, mediated through concurrent engagement. Building engagement, academic buoyancy, and foundational mathematics skills, could work synergistically to show downstream benefits for students' achievement. Highlights: Relations between academic buoyancy, engagement, and achievement, were examined. Academic buoyancy positively predicted subsequent achievement, but not vice versa. Engagement positively predicted subsequent achievement, but not vice versa. Academic buoyancy positively predicted achievement indirectly via engagement.